Inhibition of CAL27 Oral Squamous Carcinoma Cell by Targeting Hedgehog Pathway With Vismodegib or Itraconazole - Freitas, Raíza Dias; Dias, Rosane Borges; Vidal, Manuela Torres Andion; Valverde, Ludmila de Faro; Gomes Alves Costa, Rafaela; Damasceno, Andresa Karen Andrade; Sales, Caroline Brandi Schlaepfer; Siquara da Rocha, Leonardo de Oliveira; dos Reis, Mitermayer Galvão; Soares, Milena Botelho Pereira; Coletta, Ricardo Della; Pereira, Thiago Almeida; et al. (Frontiers in Oncology, 2020)
Oral Squamous Cell Carcinoma (OSCC) presents an important challenge for the health systems worldwide. Thus, unraveling the biological mechanisms involved in OSCC pathogenesis is essential to the discovery of new drugs with anticancer potential. The Hedgehog (HH) pathway has shown promising results as a therapeutic target both in vitro and in vivo. This study aimed to investigate this study was to investigate the effects of vismodegib and itraconazole on the expression of Hedgehog (HH) genes (PTCH1, SMO and GLI1), cell cycle and cell death in Oral Squamous Cell Carcinoma (OSCC) cells. An Alamar Blue assay was used to assess the cytotoxicity of vismodegib and itraconazole in a panel of oral cancer cell lines, including CAL27. The expression of HH signaling components before and after treatment with vismodegib and itraconazole at concentrations of 25 or 50 μg/mL concentrations was evaluated by qPCR. Cell cycle and apoptosis were evaluated by flow cytometry after 72h treatment with vismodegib and itraconazole (50 μg/mL). HH signaling was found to be activated in OSCC cell lines CAL27, SCC4, SCC9 and HSC3. Vismodegib and itraconazole (50 μg/ mL) were observed to significantly reduced CAL27 cell viability after 48h of treatment. Gene expression of PTCH1, SMO and GLI1 decreased in response to 24h of treatment with vismodegib or itraconazole. Furthermore, CAL27 cells exhibited alterations in morphology, cell size and cellular granularity. An increase in the Sub-G1 population was observed after treatment and both inhibitors were shown to induce apoptosis after 72h. In conclusion, the SMO inhibitors vismodegib and itraconazole demonstrably reduced the expression of HH genes in the CAL27 OSCC cell line. In addition, treatment with vismodegib and itraconazole reduced cellular viability and altered the morphology of CAL27 cells, and also induced apoptosis.